Stem cells in Urology - Syed Muhammad Nazim,; Sarfraz Ahmad, (Journal of the Pakistan Medical Association, 2023)
Stem cell research is rapidly expanding and has provided novel concepts in understanding and managing various diseases. Recent progress in translational and experimental urology has given insight about their utilization in the treatment and regeneration of urological structures. Chronic degenerative and neurological conditions affecting the lower urinary tract (LUT) are excellent targets for stem cell therapy. Their role has been particularly studied in bladder dysfunction, painful bladder syndrome, bladder outflow obstruction, stress urinary incontinence, erectile dysfunction, and urethral regeneration. However, the translation of this research in clinical domain is slow. Furthermore, regeneration of kidney using stem cells has been explored but remains challenging due to complexities of nephrons. Stem cells research in uro-oncology, especially bladder and prostate cancer, provided significant insight in understanding of pathogenesis processes and expanded potential therapeutic options. Continued...